A simulator for opportunistic networks. (29th March 2016) - Chilipirea, Cristian; Petre, Andreea‐Cristian; Dobre, Ciprian; Pop, Florin; Suciu, George
Summary: When mobile devices involved in a communication process are unable to establish a direct connection, or when communication should be offloaded to cope with large throughputs, mobile collaboration can be used to enable communication through opportunistic networks. These types of networks are formed when mobile devices communicate only using short‐range transmission protocols, usually when users are close. Routes are built dynamically, because each mobile device is acting according to the store‐carry‐and‐forward paradigm. Thus, contacts are seen as opportunities to move data towards the destination. In such networks, the routing protocol is of vital importance, and today, we witness quite a number of routing algorithms that have been proposed to maximize the success rate of message delivery whilst minimizing the communication cost. Such protocols take advantage of the devices history of contacts, or information about users carrying the mobile devices, to make their forwarding decision. This paper extends our previous work with the following: First, we describe a new simplified, fast simulator, designed to minimize the work needed to conduct extensive tests for opportunistic routing algorithm on multiple traces; next, we analyze extensively several of the most popular routing algorithms through extensive simulations conducted using our simulation platform. We highlight their pros and cons in different scenarios, considering different real‐world mobility data traces, such as Global Positioning System traces. The raw Global Positioning System traces are converted to a format based on encounters between participating entities. Copyright © 2016 John Wiley & Sons, Ltd.